A new genus in the family Flatidae with one new combination and three new species (Hemiptera: Fulgoromorpha) - Peng, Lingfei; Fletcher, Murray; Zhang, Yalin (Zootaxa, 2016)
Herbiflata gen. nov., the second genus in the tribe Nephesini from China, is erected with Hilavrita xizangensis Chou et Lu, 1981 as its type species—Herbiflata xizangensis (Chou et Lu, 1981) comb. nov. This new genus resembles Hilavrita Distant, 1906 but can be differentiated by the following characters: vertex obtusely pointed; tegmen not spotted, with orange margin; apical angle of tegmen broadly rounded; Vein ScP+R arising from one stem. Three new species, H. chromata sp. nov., H. sacra sp. nov. and H. saxeta sp. nov., are described and illustrated. A key to four species in this genus is provided.